Adócsalás és korrupció: lakossági érintettség és elfogadottság - András Semjén; István János Tóth; Márton Medgyesi; Ágnes Czibik (Hungarian Academy of Sciences, Institute of Economics, 2008)
– The paper presents survey results regarding opinions and attitudes of the 18-60 y. o. Hungarian population concerning tax evasion and corruption, while it also examines the actual and intended behavior of the economically most active segment of the population concerning these matters, and explores the socio-demographic factors determining this behavior. After presenting some basic sample characteristics, we investigate the scope and prevalence of hidden employment (both unreported employment and employment masked as contract with a subcontractor), its underlying social and economic factors and the main reasons behind accepting or turning down work offers in the hidden economy. Our results suggest that the selection of the particular form of tax sparing employment, i.e. the choice between accepting unreported employment (receiving unreported wage directly into one's own pocket) and employment masked as pretended subcontracting” is determined by the worker's socio-economic background to a great extent. Accepting unreported employment (unreported wage) is more prevalent amongst those on the periphery of the labor market, while pretended subcontracting” occurs more frequently amongst graduates and those working in public administration, health care, education and culture. We also investigate to what extent the respondents engage in purchasing products and services form the hidden economy. Men purchase from the black economy more often then women, and those living in Budapest also buy products and services there (thus evading VAT payments) more frequently than the rest of the population. Although one would probably expect that members of families with low income engage in unreported transactions more frequently than the others, our results do not support this hypothesis. We also look at the reactions of respondents to hypothetical situations in which reliance on tax evasion and/or corruption seemingly offer a relatively easy and favorable solution. Answers to questions on such hypothetic situations can serve as a control to our results on actual behavior. Those who estimate the share of population receiving income from the hidden economy higher in their neigborhood would be more likely to rely on illegal but economically favorable solutions (such as tax evasion or corruption).
Keywords: H26; H31; Z13; 330; hidden economy; unreported employment; tax evasion; corruption; population survey; Schattenwirtschaft; Schwarzarbeit; Steuerstrafrecht; Korruption; Ungarn